Compositional evolution of long-period stacking ordered structures in magnesium studied by atom probe tomography. (November 2018) - Kim, Jin-Kyung; Guo, Wei; Choi, Pyuck-Pa; Raabe, Dierk
Abstract: Mg alloys containing long-period stacking ordered (LPSO) structures are strong and ductile compared to conventional Mg alloys. We study here the compositional evolution of LPSO structures in a Mg97Y2Zn1 (at.%) alloy upon annealing at 500 °C using atom probe tomography. In the material annealed for 2.5 h, the Zn/Y ratio of the building blocks in the interdendritic LPSO phase (0.73) is close to the stoichiometric composition of Y8 Zn6 L12 clusters while that in plate-type LPSO structures (0.66) slightly deviates from the ideal value. The Y/Zn enrichment in LPSO structures in the α-Mg matrix slightly decreases with increasing annealing time. Graphical abstract: Unlabelled Image